Single Input Multi Output Switched Boost Inverter for Small Scale Solar Distributed Generation - Mr. Prakash Kerur; Prof. R.L. Chakrasli; Mr. Shivayogi S. S (Journal of Power Electronics and Devices, 2018)
This paper presents switched boost inverter for small scale roof top solar electric power generation. The traditional converter like buck or boost converter produces only dc output voltages and inverter only produces ac voltages. But proposed converter produces both ac and dc simultaneously from single input DC. With this feature SBI has more advantages compare to the conventional DC- AC or DC-DC converter. It also exhibits better electromagnetic interface when compare to conventional VSI. The size and switching losses are less. This is single stage power converter which produces both AC and DC voltages. With this feature of SBI it is used to supply the power to the grid and also we can store the power in the batteries for emergency power backup. SBI is simulated using MUTLISIM software and tested with hardware implementation.